Parental education, television exposure, and children's early cognitive, language and behavioral development - Kühhirt, Michael; Klein, Markus (Social science research, 2020)
The association between television exposure and children's development is subject to controversial debates. Heavy television exposure may be detrimental to children by overstimulating their developing brains. It may also infringe on time that children would otherwise spend on more developmentally beneficial activities or parental interactions. In the present analysis, we use data from the 2004/5 birth cohort of the Growing Up in Scotland study to investigate relations between hours of weekly television measured around the ages of two to four and as average over this period with children's linguistic, cognitive, and behavioral outcomes around the age of five. Our analysis shows differences in the level and growth of television exposure by parental education. However, we did not find any substantive associations between television exposure and children's cognitive or language ability. We found small associations of television exposure with conduct problems and prosocial behavior, particularly for children of less-educated parents. Overall, the results suggest that the impact of television on children's development is less pronounced than often assumed.